2020
DOI: 10.1186/s12992-019-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of enrollment decision in the community-based health insurance, North West Ethiopia: a case-control study

Abstract: Objective: To identify the determinants for enrollment decision in the community-based health insurance program among informal economic sector-engaged societies, North West Ethiopia. Method: Unmatched case-control study was conducted on 148 cases (member-to-insurance) and 148 controls (not-member-to-insurance program) from September 1 to October 30,2016. To select the villages and households, stratified then simple random sampling method was employed respectively. The data were entered in to Epi-info version 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
5
12
1
Order By: Relevance
“…Study participants with large family size were more likely to join CBHI scheme than those with few family size. This finding is similar with those of other studies conducted in Selected Districts of Jimma Zone [8], North West Ethiopia [21], Debub Bench district [20] and west Gojjam zone [19]. This similarity might be attributed to the excessive out of pocket expenses from medical bills that large households faced at a time of occurrences of unpredictable illnesses might lead to catastrophic health expenditure and move them to below poverty line.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study participants with large family size were more likely to join CBHI scheme than those with few family size. This finding is similar with those of other studies conducted in Selected Districts of Jimma Zone [8], North West Ethiopia [21], Debub Bench district [20] and west Gojjam zone [19]. This similarity might be attributed to the excessive out of pocket expenses from medical bills that large households faced at a time of occurrences of unpredictable illnesses might lead to catastrophic health expenditure and move them to below poverty line.…”
Section: Discussionsupporting
confidence: 90%
“…The probability of willingness to join CBHI scheme was higher among those who had experienced an illnesses in the last three months than their counter parts. This finding was supported by study conducted in Simada district [16], North West Ethiopia [21] and Cameroon [17]. This could be due to risk averse individuals are more likely to join CBHI scheme.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, this study pointed out that insufficient knowledge about health insurance is the hindering factor for uptake of health insurance. This finding is along with two studies by who reported that lack of basic knowledge and understanding about health insurance are the barriers to enrolment into health insurance (Atafu 2018;Taddesse et al, 2020). In Ghana and Ethiopia studies documented that limited knowledge about the role of insurance in terms of risk sharing and resource redistribution are likely to reduce enrolment and renewal into the health insurance (Mebratie et al, 2015;Kotoh and Geest 2016).…”
Section: Discussionsupporting
confidence: 65%
“…Our study revealed that households with a larger family size were more likely to enroll in the CBHI scheme than their counterparts. This finding was supported by studies conducted in Ethiopia and Nigeria[30, 31]. The main reason for this could be because the likelihood of having health problems in a family depends on household size.…”
Section: Discussionsupporting
confidence: 63%